Effect of interphase parameters on elastic modulus prediction for cellulose nanocrystal fiber reinforced polymer composite - Lim Joong Yeon; Kim Han-Wool; Park Min-Wook (Science and Engineering of Composite Materials, 2020)
In this study, the effective elastic modulus (Ec) of a cellulose nanocrystal fiber reinforced polymer composite was evaluated using the Mori-Tanaka and finite element (FE) model. The FE model was generated using a representative volume element with a periodic boundary condition. The mass fractions of the fiber in the composites (MFf) were set to 1, 2, and 3 wt.%. Elastic modulus values for interphase were input and were either uniform or exhibited a gradient. The E c for the uniform interphase region increased significantly with MFf, but was relatively low for interphase regions exhibiting a gradient. The results show that interphase parameters must be considered carefully when predicting Ec using the FE model.